2005
DOI: 10.1677/joe.1.06131
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone in health and disease

Abstract: Thyroid disease is common, affecting around 2% of women and 0·2% of men in the UK. Our understanding of the effects of thyroid hormones under physiological circumstances, as well as in pathological conditions, has increased dramatically during the last two centuries and it has become clear that overt thyroid dysfunction is associated with significant morbidity and mortality. Both hypoand hyperthyroidism and their treatments have been linked with increased risk from cardiovascular disease and the adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(156 citation statements)
references
References 107 publications
4
139
0
13
Order By: Relevance
“…We also found that p,p′-DDE was associated with increased free T 4 and total T 3 , and inversely associated with TSH. Studies on adverse health effects associated with small changes in thyroid hormones in humans are limited (Boelaert and Franklyn 2005;Surks et al 2004), and the changes found in the present study may not be clinically important at the individual level. However, due to the pervasiveness of exposure to these compounds there may be consequences related to small changes in thyroid hormone levels among entire subsets of the population.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We also found that p,p′-DDE was associated with increased free T 4 and total T 3 , and inversely associated with TSH. Studies on adverse health effects associated with small changes in thyroid hormones in humans are limited (Boelaert and Franklyn 2005;Surks et al 2004), and the changes found in the present study may not be clinically important at the individual level. However, due to the pervasiveness of exposure to these compounds there may be consequences related to small changes in thyroid hormone levels among entire subsets of the population.…”
Section: Discussionmentioning
confidence: 51%
“…Although the consequences of sub-clinical changes in thyroid hormones are currently not well understood (Boelaert and Franklyn 2005;Surks et al 2004), factors associated with any alteration in thyroid hormone levels are of concern. Several environmental agents, most notably organochlorine pesticides and polychlorinated biphenyls (PCBs), have been found to influence thyroid hormone activity and metabolism (Zoeller 2005;Qatani et al 2005;Bogazzi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of thyroid function on cardiovascular morbidity and mortality has received much atten-tion over the past years 1,2) . Overt hypothyroidism is associated with abnormal lipid metabolism and impaired endothelial function as well as increased risk of atherosclerosis and ischemic heart disease 3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals, neuroendocrine feedback mechanisms ensure that T3 and T4 are maintained within normal limits. Levels of THs within the normal range are crucial for the maintenance of various physiological and cognitive functions such as attention, memory, and mood (for review see Boelaert and Franklyn, 2005;Smith et al, 2002).…”
Section: Introductionmentioning
confidence: 99%